Surface Modification Of Carbon Materials For Hydrogen Storage - Sanip, Suhaila M.; Sulaiman, Yusran; Buang, Nor Aziah; Aziz, Madzlan; Abdul Majid, Zaiton; Ismail, Ahmad Fauzi (2004)
Hydrogen is a great energy carrier for both mobile and stationary power generation. However, the availability of hydrogen as a power source is hindered due to lack of cost, effectiveness and safe storage solutions. Thus, one of the key areas for colnmercialization of hydrogen-powered vehicles is the development of safe methods for hydrogen storage. Gas-on-solid adsorption presents itself as the safest method for hydrogcn storage. It is a more energy efficient method than cither chemical or mctal hydrides as well as con~pressed gas storagc. Much work has becn done to study the hydrogen storage properties of high surface area carbon niatcrials. In this work, the effect of pretreatment on activated carbons and graphite was studied. Both carbon materials were treated with 4 M hydrochloric acid and heat at 600 " C in an inert atmosphere condition respectively. The surface area and morphology of the treated samples were thoroughly investigated using nitrogen adsorption and scanning electron microscopy techniques. It was found that acid treatment increases the surface area of activated carbon due to the opening up of the internal surface area and widening of the pores. Graphite however, displayed a smaller surface area after acid treatment as a result of the disruption of the ordered lattice layer. An increase in the surface area was also observed for both carbon materials after heat treatment thereby enhancing their adsorption properties.